Optimasi Penjadwalan Proyek Pembangunan Jembatan Pada Tol Jakarta - Cikampek II Selatan Paket III Dengan Metode PERT (Program Evaluation And Review Technique) (Studi Kasus PT.XYZ) - Aldi Kurniawan; Daisy Ade Riany Diem; Asep Hermawan; Widowati, Imas (Jurnal Teknologika, 2024)
A construction project is a temporary activity that takes place within a limited period of time and has been determined. In carrying out a project, it is carried out based on the plans that have been made by the project planner, one form of planning a project is the project scheduling of as a toll road business entity is currently carrying out detailed engineering design activities in which the implementation of the project has been delayed. Completion of new projects has reached 85%, one example is the Bridge work (Sta 54+600). In carrying out the bridge work (Sta 54+600) it is planned that the working period is 264 days. However, the implementation of the bridge work (Sta 54 + 600) was delayed by 15 working days, so the planned time for the bridge work was not optimal. in Bridge Construction using the PERT (Project Evaluation and Review Technique) method, there are critical paths on Access Roads, Mobilization, Digging Pile Caps, LC Pile Caps, Formwork Pile Caps, Cast Columns, Erection Girders, Land Clearing, Cast Slabs get an opportunity probability of 0.6179 which meaning that there is a chance that 61.79% of bridge construction projects (Sta 54+600) have a chance to be completed with an optimal duration of 252 days.